THE SECURITY PRIORITY OF TURKEY AND THE COUNTRIES OF THE MIDDLE EAST - Murtalibova Malika Mirmaksudovna (Journals Park Publishing, 2024)
This article discusses the problem of ensuring regional security in the Middle East region is extremely urgent. Historically, this region is the leader in the number of crisis and conflict situations. The main reason for such "leadership" is the lack of special tools for maintaining stability in these regions, as well as the lack of a general security system that has never been rationalized in the region. For a long time, the Middle East region has been the center of concentration of threats to international security.
Keywords: The Middle East, The Arab Spring, Ankara, Baghdad, security, Qatar.